2018
DOI: 10.1007/s00208-018-1735-3
|View full text |Cite
|
Sign up to set email alerts
|

A lower bound on the canonical height for polynomials

Abstract: We prove a lower bound on the canonical height associated to polynomials over number fields evaluated at points with infinite forward orbit. The lower bound depends only on the degree of the polynomial, the degree of the number field, and the number of places of bad reduction. In the dynamical setting, Silverman has made the following conjecture [15, §4.11].Conjecture 1.1. Let h M d be the height function associated to an embedding of the space of degree d ≥ 2 rational maps M d into projective space, and let K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…For example, the map f = [X 2 , Y 2 , γZ 2 ] has height roughly h(γ), while the f -orbit of the point P = [α, 1, 0] has canonical heightĥ f (P ) = h(α), so we can make h M (f ) arbitrarily large whileĥ f (P ) remains bounded. Ingram [116] and Looper [155] have proven weak versions of Conjecture 16.3 for polynomial maps f of P 1 , where the constants depend also on the number of primes of bad reduction of f .…”
Section: Conjecture 162 (Dynamical Lehmer Conjecturementioning
confidence: 99%
“…For example, the map f = [X 2 , Y 2 , γZ 2 ] has height roughly h(γ), while the f -orbit of the point P = [α, 1, 0] has canonical heightĥ f (P ) = h(α), so we can make h M (f ) arbitrarily large whileĥ f (P ) remains bounded. Ingram [116] and Looper [155] have proven weak versions of Conjecture 16.3 for polynomial maps f of P 1 , where the constants depend also on the number of primes of bad reduction of f .…”
Section: Conjecture 162 (Dynamical Lehmer Conjecturementioning
confidence: 99%
“…Besides the input of height machinery and bounds on heights of preperiodic points of polynomial functions (e.g. from [27,37]), one of the other main ideas is to show that the prime factors of differences of preperiodic points z i − z j are typically in the places of bad reduction when f has many preperiodic points. The abcd conjecture (Conjecture 2.9) can then be applied to combinatorial "polygons" constructed from preperiodic points giving points on the projective hyperplanes H. Following Looper [38] with some case-by-case calculations, Panraksa [54] showed that the usual abc conjecture implies that there are no rational non-fixed periodic points for largedegree unicritical polynomials.…”
Section: Conjecture 35 (Dynamical Uniform Boundedness Conjecturementioning
confidence: 99%
“…Besides the input of height machinery and bounds on heights of preperiodic points of polynomial functions (e.g. from [Ing09,Loo19]), one of the other main ideas is to show that the prime factors of differences of preperiodic points z i − z j are typically in the places of bad reduction when f has many preperiodic points. The abcd conjecture (Conjecture 2.9) can then be applied to combinatorial "polygons" constructed from preperiodic points giving points on the projective hyperplanes H.…”
Section: Uniform Boundedness Of Preperiodic Pointsmentioning
confidence: 99%